INDICATORS OF THE QUALITY OF DETECTION OF LETTERS OF THE ALPHABET BY A SPECIALIZED MEANS OF INTERCEPTING INFORMATION FROM MONITOR SCREENS ON RARE-CRYSTAL STRUCTURES - Yaremchuk, Yurii; Evgrafov , Dmitry (Ukrainian Information Security Research Journal, 2022)
The block diagram of a modern means of special reconnaissance, which allows intercepting spurious electromagnetic radiation from monitor screens on rare-crystal structures, is considered. It is shown that modern digital signal processing technologies make it possible to implement coordinated reception of information leakage signals using digital filters with a comb amplitude-frequency characteristic. The spectral representation of information leakage signals from monitor screens, on which one of the letters of the Ukrainian alphabet is displayed, is considered. It is proved that even for a low resolution of the spectral representation of letters, they have a characteristic form. The dispersion at the output of the linear system of a specialized reconnaissance means was found, which is hundreds of times less than the dispersion of a conventional broadband signal receiver. The view of the letters of the alphabet intercepted from the monitor screen on rare-crystal structures for different signal-to-noise ratios at the output of the linear system by the receiver of a specialized reconnaissance tool is modeled. The probabilities of false alarms are found during the detection of information leakage signals, depending on the normalized detection threshold. For a fixed normalized detection threshold, the probabilities of correct detection of one or another letter of the Ukrainian alphabet against the background of internal noises of a specialized reconnaissance means are calculated. For a fixed signal-to-noise ratio and a fixed false alarm, the probabilities of correct detection of different letters of the Ukrainian alphabet are found.